2020
DOI: 10.1155/2020/8844698
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio in Blood to Distinguish Lung Cancer Patients from Healthy Subjects

Abstract: Objective. Inflammation-driven markers play a crucial role in tumorigenesis and tumor progression. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in blood are systemic inflammatory response markers. Some reports have showed that NLR and PLR are related to a poor prognosis in patients with lung cancer. However, little studies have reported whether NLR and PLR can be diagnostic markers for lung cancer. The aim of the current study is to investigate the roles of NLR and PLR in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…However, there was no obvious difference between healthy patients and benign lung disease patients, which to some extent confirmed the role of inflammatory indicators in the progression of LUAD. Zhu et al 33 also reported that NLR and PLR could be used as diagnostic markers for lung cancer patients to distinguish healthy subjects. In addition, we found that serum albumin and LDH were significantly different among the three groups, suggesting the role of albumin and LDH in the occurrence and development of pulmonary disease, especially LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no obvious difference between healthy patients and benign lung disease patients, which to some extent confirmed the role of inflammatory indicators in the progression of LUAD. Zhu et al 33 also reported that NLR and PLR could be used as diagnostic markers for lung cancer patients to distinguish healthy subjects. In addition, we found that serum albumin and LDH were significantly different among the three groups, suggesting the role of albumin and LDH in the occurrence and development of pulmonary disease, especially LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation induces carcinogenic mutagenesis and regulates carcinogenesis of CRC [ 25 27 ]. Common inflammatory ratios such as neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, and lymphocyte to monocyte ratio show moderate diagnostic efficacies in distinguishing glioma, lung cancer, and healthy subjects, respectively [ 28 , 29 ]. Our previous study also found that circulating FPR was superior to AFR and NLR in diagnosing stage I–IV CRC in healthy individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these criteria are based on disease status, comorbidities or other pre-HSCT parameters. Recently, parameters reflecting the inflammatory status such as NLR, MLR and PLR have been recognized to play an important role to identify patients with higher risk of NRM, relapse and impaired OS especially in solid cancers or solid organ www.nature.com/scientificreports/ transplantation settings 6,7,[18][19][20][21] . Data in hematological diseases, especially in autologous or allogeneic stem cell transplantation are rare or missing.…”
Section: Discussionmentioning
confidence: 99%